2011
DOI: 10.1158/0008-5472.can-11-1301
|View full text |Cite
|
Sign up to set email alerts
|

Egfl7 Promotes Tumor Escape from Immunity by Repressing Endothelial Cell Activation

Abstract: Downregulating the leukocyte adhesion molecules expressed by endothelial cells that line tumor blood vessels can limit the entry of immune effector cells into the tumor mass, thereby contributing to tumoral immune escape. Egfl7 (also known as VE-statin) is a secreted protein specifically expressed by endothelial cells in normal tissues and by cancer cells in various human tumors. High levels of Egfl7 correlate with higher tumor grade and poorer prognosis. Here we show that expression of Egfl7 in breast and lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
86
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 26 publications
12
86
2
2
Order By: Relevance
“…High EGFL7 expression has been associated with increased tumor growth partly mediated by preventing invasion of immune cells into the tumor (2). These previous findings taken together support the plausibility of our current results demonstrating increased efficacy of an anti-VEGF-A regimen in tumors with low EGFL7 VA, and draws attention to the current testing of an anti-EGFL7 antibody in combination with chemotherapy plus anti-VEGF-A in patients with mCRC (CONGO trial).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…High EGFL7 expression has been associated with increased tumor growth partly mediated by preventing invasion of immune cells into the tumor (2). These previous findings taken together support the plausibility of our current results demonstrating increased efficacy of an anti-VEGF-A regimen in tumors with low EGFL7 VA, and draws attention to the current testing of an anti-EGFL7 antibody in combination with chemotherapy plus anti-VEGF-A in patients with mCRC (CONGO trial).…”
Section: Discussionsupporting
confidence: 87%
“…The EGFL7 protein is related to fundamental angiogenic mechanisms responsible for vascular tube formation, vascular integrity, guiding migration of endothelial cells (EC) during the sprouting process, and the suppression of tumor infiltration by immune cells (2)(3)(4)(5). Preclinical studies indicate that miR126, which is transcribed from intron 7 in the EGFL7 gene, is important for maintaining EC proliferation and migration, vascular integrity, VEGF-A signaling, and tumor growth (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Egfl7 expression in human cancer needs to be carefully analyzed as Egfl7 may play complex roles in cancer biology. Indeed, Egfl7 has different effects on tumor cells depending on their origin: Egfl7 increases tumor cell migration of hepatocarcinoma cells (12) while it has no effects on breast cancer cell migration (18). Here, we found that Egfl7 is not associated with a more advanced disease when expressed by human breast cancer epithelial cells.…”
Section: Discussionmentioning
confidence: 58%
“…EGFL7 is a secreted signaling factor derived from endothelial cells that controls blood vessel formation (15); this protein is upregulated during angiogenesis and is associated with blood vessel lumen formation, vascular integrity and the regulation of the collective migration of endothelial cells during the blood vessel sprouting process through the restriction of their spatial distribution (17)(18)(19). In certain types of human cancer cells, EGFL7 suppresses the activation of endothelial cells and inhibits the expression of specific endothelial adhesion molecules (VCAM1 and ICAM1); it also reduces the adhesion of lymphocytes on the endothelium and consequently decreases vascular tightness (20).…”
Section: No Of Patients --------------------------------------------mentioning
confidence: 99%
“…EGFL7 is upregulated during angiogenesis and is involved in the regulation of endothelial cell migration during the sprouting process, blood vessel lumen formation and maintenance of vascular integrity (17)(18)(19). In certain types of human cancer cells, EGFL7 inhibits the activity of endothelial cell adhesion molecules [such as vascular cell adhesion molecule 1 (VCAM1) and intercellular adhesion molecule 1 (ICAM1)], which leads to decreased vascular tightness (increased vascular permeability), increased immune evasion and increased tumor growth (20). Decreased blood vessel integrity is frequently observed in malignant tumors (21).…”
Section: Introductionmentioning
confidence: 99%